PENGARUH LINGKUNGAN KERJA DAN JOB EMBEDDEDNESS TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. MEDAN JAYA PANGAN MUTU - Nasution, Kasturi Handayani; Pasaribu, Fajar; Sabrina, R (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
The purpose of this study is to test and analyze the effect of work environment and job embeddedness on turnover intention through job satisfaction as a mediator. All employees of PT Medan Jaya Pangan Mutu are the research subjects. The saturated sample method was used to select a sample of 36 individuals. PLS (Partial Least Square) software was used to process the data in this study. The results of this study indicate that work environment, job embeddedness, and job satisfaction directly affect turnover intention; job satisfaction indirectly affects work environment and job embeddedness on turnover intention at PT Medan Jaya Pangan Mutu.